SIDT2 mediates gymnosis, the uptake of naked single-stranded oligonucleotides into living cells. Issue 11 (2nd November 2017) - Takahashi, Masayuki; Contu, Viorica Raluca; Kabuta, Chihana; Hase, Katsunori; Fujiwara, Yuuki; Wada, Keiji; Kabuta, Tomohiro
ABSTRACT: Single-stranded oligonucleotides (ssOligos) are efficiently taken up by living cells without the use of transfection reagents. This phenomenon called 'gymnosis' enables the sequence-specific silencing of target genes in various types of cells. Several antisense ssOligos are used for the treatment of human diseases. However, the molecular mechanism underlying the uptake of naked ssOligos into cells remains to be elucidated. Here, we show that systemic RNA interference deficient-1 (SID-1) transmembrane family 2 (SIDT2), a mammalian ortholog of the Caenorhabditis elegans double-stranded RNA channel SID-1, mediates gymnosis. We show that the uptake of naked ssOligos into cells is significantly downregulated by knockdown of SIDT2. Furthermore, knockdown of SIDT2 inhibited the effect of antisense RNA mediated by gymnosis. Overexpression of SIDT2 enhanced the uptake of naked ssOligos into cells, while a single amino acid mutation in SIDT2 abolished this effect. Our findings highlight the mechanism of extra- and intracellular RNA transport and may contribute to the further development of nucleic acid-based therapies.